Comparison of Tier 1 and 2 Methodologies for Estimating Intake and Enteric Methane Emission - Balcha, Endale; Ndung’u, Phyllis; Wilkes, Andreas; Getahun, Daniel; Graham, Michael; Leitner, Sonja; Marquardt, Svenja; Mulat, Daniel; Merbold, Lutz; Worku, Tigist; Arndt, Claudia (International Livestock Research Institute, 2023)
The objective of this study was to compare gross energy intake (GEI; MJ/animal/day) and enteric methane (CH4) emission factors (EF; CH4 kg/animal/year) of different cattle categories from smallholder systems in Ethiopia based on Intergovernmental Panel on Climate Change (IPCC) Tier 1, IPCC Tier 2, and International Livestock Research Institute (ILRI) Tier 2 methodology. The ILRI Tier 2 methodology uses calculations that are based on or modified from equations published in ‘Nutrient Requirements of Domesticated Ruminants’ (CSIRO 2007). In comparison to IPCC, the ILRI methodology is based on metabolizable and not net energy requirements of the animal. Data from Ethiopian smallholder systems were collected four times corresponding to the beginning and end of the three seasons (spring, summer and winter) to account for the effect of seasonality on animal liveweight, diet and performance. There was a high correlation of GEI between IPCC and ILRI Tier 2 methodology (R2=0.87). However, the IPCC Tier 2 methodology estimated a higher GEI than the ILRI methodology (P<0.05; based on one-sample t-test). The mean difference in GEI was 28 MJ/animal/day (s.d. 18.2), which was 27 and 38% of the average GEI estimated by IPCC and ILRI methodology, respectively. Compared to ILRI methodology, IPCC methodology used a greater methane conversion factor (Ym; 7.0 vs 6.3% of GE in feed converted to CH4). Because of the greater GEI and Ym, the IPCC methodology estimated on average 49% greater EFs than the ILRI methodology (48.4 vs 32.4 CH4/animal/day, P<0.05). The EFs calculated across all cattle categories (adult females, intact and castrated males, heifers, young makes, and calves) for IPCC Tier 1 (2019) default EFs were found to be 23-38 and 38-59% lower for the IPCC and ILRI Tier 2 methodology, respectively. Similarly, when compared to Tier 1 methodology, IPCC and ILRI Tier 2 methodology estimated 27 and 51% lower total animal emission from smallholder cattle systems, respectively. The observed difference between the methodologies was based on the differences in predicted feed intakes and Ym. Hence, the predictions by Tier 1 and 2 methodologies need to be compared to in vivo intake and CH4 measurements to determine which methodology predicts GEI and Ym more accurately.